The prevalence and influencing factors for child neglect in a rural area of Anhui province: a 2-year follow-up study. (February 2018) - Zhao, F.; Bi, L.; Chen, M.-C.; Wu, Y.-L.; Sun, Y.-H.
Abstract: Objectives: The purpose of the current study was to identify the change of prevalence and influencing factors for child neglect in a rural area of Anhui province through the 2-year follow-up study. Study design: Longitudinal study with 2-year follow-up. Methods: Analyses were based on data from a longitudinal study, performed in five elementary schools and three secondary schools in Changfeng County. A total of 816 children aged between 7 and 16 years completed the three assessments during the period of 2009–2011. Generalized estimating equations (GEEs) were applied to identify the influencing factors of child neglect. Results: The prevalence of child neglect was 67.8%, 56.6%, and 57.7% at the three assessments, respectively. There were 272 children (33.3%) having consistently experiencing neglect during three assessments and 106 (13.0%) children had not suffered from neglect during three assessments. Among 553 participants who experienced neglect at the first assessment, 105 (19.0%) children no longer met the diagnosis at the next two assessments. Fifty-two children who did not suffer from neglect at the first assessment experienced neglect at the final assessment. The results of GEEs showed that child neglect was clearly associated with age (odds ratio [OR] = 0.95, 95% confidence interval [CI] = 0.92–0.99, P = 0.016), male gender (OR = 1.20, 95% CI = 1.00–1.43, P = 0.047), siblings (OR = 1.26, 95% CI = 1.03–1.55, P = 0.028), parental marital disruption (OR = 2.02, 95% CI = 1.09–3.78, P = 0.027), left-behind status (OR = 1.26, 95% CI = 1.06–1.49, P = 0.008), severe family dysfunction (OR = 1.46, 95% CI = 1.03–2.07, P = 0.035), quality of life (OR = 0.98, 95% CI = 0.98–0.99, P < 0.001), positive coping styles (OR = 0.97, 95% CI = 0.94–0.99, P = 0.001), and negative coping styles (OR = 1.03, 95% CI = 1.02–1.05, P < 0.001). Conclusion: Our studies detected the decreased prevalence of child neglect across the three assessments. Additionally, some sociodemographic, psychosocial and family risk factors of child neglect were identified, which will be helpful for child neglect prevention strategies development and implementation in China. Highlights: A 2-year follow-up study was performed in a rural area of Anhui, China. The longitudinal study was based on the unique social and cultural background. The 2-year follow-up study identified the dynamic change of child neglect.